Biotechnological synthesis of Pd/Ag and Pd/Au nanoparticles for enhanced Suzuki–Miyaura cross‐coupling activity. Issue 6 (15th March 2021) - Kimber, Richard L.; Parmeggiani, Fabio; Neill, Thomas S.; Merroun, Mohamed L.; Goodlet, Gregory; Powell, Nigel A.; Turner, Nicholas J.; Lloyd, Jonathan R.
Summary: Bimetallic nanoparticle catalysts have attracted considerable attention due to their unique chemical and physical properties. The ability of metal‐reducing bacteria to produce highly catalytically active monometallic nanoparticles is well known; however, the properties and catalytic activity of bimetallic nanoparticles synthesized with these organisms is not well understood. Here, we report the one‐pot biosynthesis of Pd/Ag (bio‐Pd/Ag) and Pd/Au (bio‐Pd/Au) nanoparticles using the metal‐reducing bacterium, Shewanella oneidensis, under mild conditions. Energy dispersive X‐ray analyses performed using scanning transmission electron microscopy (STEM) revealed the presence of both metals (Pd/Ag or Pd/Au) in the biosynthesized nanoparticles. X‐ray absorption near‐edge spectroscopy (XANES) suggested a significant contribution from Pd(0) and Pd(II) in both bio‐Pd/Ag and bio‐Pd/Au, with Ag and Au existing predominately as their metallic forms. Extended X‐ray absorption fine‐structure spectroscopy (EXAFS) supported the presence of multiple Pd species in bio‐Pd/Ag and bio‐Pd/Au, as inferred from Pd–Pd, Pd–O and Pd–S shells. Both bio‐Pd/Ag and bio‐Pd/Au demonstrated greatly enhanced catalytic activity towards Suzuki–Miyaura cross‐coupling compared to a monometallic Pd catalyst, with bio‐Pd/Ag significantly outperforming the others. The catalysts were very versatile, tolerating a wide range of substituents. This work demonstrates a green synthesis method for novel bimetallic nanoparticles that display significantly enhanced catalytic activity compared to their monometallic counterparts. Abstract : This article reports the biotechnological synthesis of novel bimetallic nanoparticles which display significantly enhanced catalytic activity in Suzuki–Miyaura couplings, compared to their monometallic counterparts. In particular, the biosynthesised Pd/Ag was found to be very versatile, tolerating a range of substituents and generating products with a good to excellent yields, including pharmaceutically relevant compounds.